Fraud In The Provision of Health Services In Hospitals During The Covid-19 Pandemic: The Government Sector - Elna Marsye Pattinaja; Fanny Monica Anakotta; Hempry Putuhena; Muhammad Fadila Laitupa; Sujatmiko Wibowo (Khazanah Sosial, 2023)
Fraud is currently rife, not only in the private sector but also in the government sector. The government sector, which is the central point in this research, is the world of health, especially hospitals, related to procuring goods and services for covid 19. This study aimed to analyze the factors that affect the procurement of goods and services during the covid 19 pandemic. This casual-comparative research type is research with the characteristics of the problem in the form of a cause-and-effect relationship between two or more variables. The study was conducted at six government hospitals in Maluku Province. The study results indicate significant fraud related to procuring goods and services for covid 19. Thus, the quality of the committee, systems and procedures, environment, internal control, and organizational commitment affect the prevention of fraud in procuring goods in hospitals in Maluku province, Indonesia.